Energy relaxation for hot Dirac fermions in graphene and breakdown of the quantum Hall effect - Baker, A; Alexander-Webber, J; Altebaeumer, T; Nicholas, R (2012)
Energy loss rates for hot carriers in graphene are experimentally investigated by observing the amplitude of Shubnikov-de Haas oscillations as a function of electric field. The carrier energy loss in graphene follows the predictions of deformation potential coupling going as ∼T4 at carrier temperatures up to ∼100 K, and that deformation potential theory, when modified with a limiting phonon relaxation time, is valid up to several hundred Kelvin. Additionally we investigate the breakdown of the quantum Hall effect and show that energy loss rates in graphene are around ten times larger than GaAs at low temperatures. This leads to significantly higher breakdown currents per micrometer, and we report a measured breakdown current of 8 μA/μm. © 2012 American Physical Society.